Financial safety indicators for the Iraqi banking sector from 2005 to 2018 - Jwaid, Samaa Mousa; Mahdi, Sabah Raheem (International Journal of Psychosocial Rehabilitation, 2020)
Financial safety indicators were considered indicators of financial safety, evaluates and monitors the strengths and weaknesses of financial systems, and the great importance of relationship of banks with supervisory policy , the development of banking supervision was linked to developments in the banking activities, the banking institutions in Iraq was importance of special legislation has been drawn up, started from defining the bank and how to establish, also set supervisory standards for early warning used to measure the banking safety performance, these parameters were taken as indicators to assess the performance of banks and discover errors in order not to fall into financial problems that lead to collapse.